(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The best wave energy resources are typically found far from land, especially in the far southern latitudes. However, these optimal locations often lie outside any single nation’s exclusive economic zone (EEZ) and are located in deep ocean waters, though a few places stand out, namely Kerguelen Islands, the southern coast of Chile and the southern tip of New Zealand. The Kerguelen Islands are situated in a prime wave energy location, with a potential capacity factor exceeding 90% when using best of breed point-absorber wave energy converters (WECs). This could result in a levelised cost of electricity of 31.4 €/MWh by 2050. An earlier study showed that the Kerguelen Islands could support up to 7 GW of installable wave power capacity, utilising only 15% of the EEZ. To evaluate the feasibility of establishing an energy hub on Kerguelen Islands, a scenario was developed using the EnergyPLAN modelling software. The scenario involves producing e-fuels and e-chemicals, which will be essential for sectors like marine and aviation transportation and chemicals as the world transitions to a defossilised economy. This analysis assumes that the islands could supply fuel for East Asia, particularly Japan, South Korea, and Taiwan. By 2050, the 7 GW wave power system could meet 3% of the demand for e-fuels and e-chemicals in these countries, producing 3.5 TWhth,LHV of e-kerosene, 2.6 TWhth,LHV of e-diesel, 19 TWhth,LHV of e-methanol, 2.5 TWhth,LHV of e-LNG, and 4.9 TWhth,LHV of e-ammonia. The cost projections for 2050 suggest that e-fuels and e-chemicals produced from Kerguelen Islands could be highly competitive, with projected costs of 95.0 €/MWh for e-kerosene and e-diesel, 78.7 €/MWh for e-methanol, 64.5 €/MWh for e-LNG, and 68.4 €/MWh for e-ammonia. In addition to wave power, the system would incorporate 2 GWhcap of battery storage and 50 GWh of underground rock cavern hydrogen storage, further enhancing the energy hub’s capacity and flexibility. These costs, assumed for 2050, are projected to be competitive compared to leading global sites, such as the Atacama Desert, which has excellent solar PV resources. For comparison, the Atacama Desert’s e-fuels production cost is estimated to range from 70-75 €/MWh, e-methanol is between 49-57 €/MWh and e-ammonia at 53 €/MWh. However, the costs mentioned above do not include shipping costs. Shipping costs for ammonia for 10,000 km to East Asia could add up to 8 €/MWh, while shipping costs for methanol could add up to 4 €/MWh. For the Kerguelen Islands an attractive business model could be established to diversify the global e-fuels and e-chemicals production that may largely shift towards solar energy. This creates a promising opportunity for investment in a gigawatt-scale energy hub for e-fuels and e-chemicals on Kerguelen Islands, including the necessary infrastructure for shipping and workforce to maintain such a system.